Effect of myocardial infarction on the occurrence of erectile dysfunction - Enisa Hodžić; Adnan Durek; Edin Begić; Nirvana Šabanović Bajramović; Azra Durak Nalbantić (Medicinski glasnik, 2018)
Aim: To investigate etiological link between acute myocardial infarction (AMI) and the accompanying impotence/erectile dysfunction (ED). Methods: Study included 99 male patients (48 who had AMI-patient group, and 51 healthy examinees without previous cardiovascular disease-control group). All patients completed a standardized questionnaire, the International Index of Erectile Function (IIEF-5). Results: Older patients had significantly lower IIEF-5 score (negative correlation) (p <0.05), but higher ED degree (significant positive correlation) (rho=0.522; p=0.0001). In the patient group, 37 (77.1%) patients had ED, while in the control group it was found in 26 (51%) examinees (p<0.05). A clear correlation was found between incidence of ED and diabetes, dyslipidaemia, hypertension and positive family history (they were more common in patients with ED, with no statistically significant difference). There was no statistically significant difference between patients with ED and patients without ED according to the beta-blocker usage (p=0.824): ED was reported in 11 (68%) patients in the group who used carvedilol, 14 (82.3%) in the group who used metoprolol, and nine (81.8%) who used nebivolol. Conclusion: Myocardial infarction as well as age are directly related to the occurrence of ED. Cardiovascular risk factors are in direct correlation for the occurrence of erectile dysfunction after myocardial infarction.
Keywords: cardiovascular disease; impotence; risk factors